2010
DOI: 10.1007/s13238-010-0132-9
|View full text |Cite
|
Sign up to set email alerts
|

Essential residues for the enzyme activity of ATP-dependent MurE ligase from Mycobacterium tuberculosis

Abstract: The emergence of total drug-resistant tuberculosis (TDRTB) has made the discovery of new therapies for tuberculosis urgent. The cytoplasmic enzymes of peptidoglycan biosynthesis have generated renewed interest as attractive targets for the development of new anti-mycobacterials. One of the cytoplasmic enzymes, uridine diphosphate (UDP)-MurNAc-tripeptide ligase (MurE), catalyses the addition of meso-diaminopimelic acid (m-DAP) into peptidoglycan in Mycobacterium tuberculosis coupled to the hydrolysis of ATP. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Mahapatra et al (2000) reported that MurC was able to incorporate glycine (Gly) and L-Ala to UDP-MurNAc in both M. tuberculosis and M. leprae [13]. Our investigation of the structural and functional characterization of MurE from M. tuberculosis [14], [15] revealed that MurE was only active in the presence of its specific natural substrates: uridine-diphospho- N -acetylmuramoyl-L-alanine-D-glutamate (UDP-MurNAc-L-Ala-D-Glu), m -DAP and ATP. In this study, we comprehensively examine and compare the activity of all Mur synthetases in M. tuberculosis with respect to their natural substrates.…”
Section: Introductionmentioning
confidence: 78%
“…Mahapatra et al (2000) reported that MurC was able to incorporate glycine (Gly) and L-Ala to UDP-MurNAc in both M. tuberculosis and M. leprae [13]. Our investigation of the structural and functional characterization of MurE from M. tuberculosis [14], [15] revealed that MurE was only active in the presence of its specific natural substrates: uridine-diphospho- N -acetylmuramoyl-L-alanine-D-glutamate (UDP-MurNAc-L-Ala-D-Glu), m -DAP and ATP. In this study, we comprehensively examine and compare the activity of all Mur synthetases in M. tuberculosis with respect to their natural substrates.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, presence of divalent cations was found to be an absolute requirement for their activities. Also higher concentrations of ATP and UDP-sugar substrates were inhibitory for the activities of all ATP dependent Mur ligases suggesting a stringent control of the cytoplasmic steps of peptidoglycan biosynthetic pathway in M. tuberculosis [23][24][25].…”
Section: Target Based Approach: Validation Of Novel Therapeutic Targementioning
confidence: 99%
“…Two crystal structures of Mtb-MurE have been solved with different substrates bound to it, and essential residues have been determined for this enzyme by mutation studies [23,24]. A number of initial hits against the Mtb-MurE enzyme have been reported by us recently [28][29][30] and some of these agents are also antibacterial against whole-cell M. tuberculosis, are now part of medicinal chemistry projects to optimize these hits.…”
Section: Target Based Approach: Validation Of Novel Therapeutic Targementioning
confidence: 99%
“…The structure of murE has been resolved to 3A and shows an accessible active pocket site that can be exploited for drug design. 124,125 Enzymatic inhibition of MurE from M. tuberculosis was observed with the extracts from Columbian plants and chemically synthesized quinolone compounds thereby demonstrating that the ligases can serve as drug targets. [126][127][128][129] Additionally, as cell division and cell wall biogenesis are stringently controlled, co-operative processes, it is no surprise to find the mur ligase genes clustered in the division cell-wall (dcw) operon, further indicating that targeting this pathway will have knock-on effects on co-regulated pathways.…”
Section: The Search For Novel Therapeutic Targetsmentioning
confidence: 99%